2016
DOI: 10.1007/s00268-016-3449-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Intraoperative Workloads Across the Surgical Team Roles: Room for Better Balance?

Abstract: BackgroundSurgical performance, provider health, and patient safety can be compromised when workload demands exceed individual capability on the surgical team. The purpose of this study is to quantify and compare intraoperative workload among surgical team members.MethodsObservations were conducted for an entire surgical day for 33 participating surgeons and their surgical team at one medical institution. Workload (mental, physical, case complexity, distractions, and case difficulty) was measured for each surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 67 publications
2
59
1
4
Order By: Relevance
“…Despite more than 550 studies using NASA‐TLX reported in the past 20 years, few have proposed the workload redline when using this tool – a point on the scale that indicates when the workload is considered so high that it may affect human performance. A modified version of NASA‐TLX was developed and validated specifically to capture the surgical context, the Surgery Task Load Index (SURG‐TLX). In two of the reviewed studies, the NASA‐TLX questionnaire was used to capture surgeons' cognitive load over repeated training sessions, and correlated with technical performance and errors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite more than 550 studies using NASA‐TLX reported in the past 20 years, few have proposed the workload redline when using this tool – a point on the scale that indicates when the workload is considered so high that it may affect human performance. A modified version of NASA‐TLX was developed and validated specifically to capture the surgical context, the Surgery Task Load Index (SURG‐TLX). In two of the reviewed studies, the NASA‐TLX questionnaire was used to capture surgeons' cognitive load over repeated training sessions, and correlated with technical performance and errors.…”
Section: Resultsmentioning
confidence: 99%
“…Only five studies (6 per cent) assessed the cognitive load of multiple operating theatre team members besides the surgeon. Team members included registered nurses (3 studies), anaesthetists (3 studies), registered nurse anaesthetists (2 studies), theatre nurses (2 studies), scrub nurses (2 studies), physician assistants (1 study), surgical technicians (2 studies), circulating nurses (1 study) and perfusionists (1 study).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There exist effective tools to assess quality and safety in the OR: adverse event measurement allows identification of potential errors in the surgical process, 3 workload and stress assessment by validated scales points out their negative impact on surgical performance. 8,9,10 It is now accepted that errors resulting from adverse events are mainly secondary to a lack of non-technical skills (NTS). 4 NTS are divided into cognitive (situation awareness, mental readiness, assessing risks…) and interpersonal (communication, leadership, teamwork, planning…) skills.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for errors, crashes, accidents and disasters made by human can be due to unbalance mental workload resulting in overload and underload situations exposing operators to approach or exceed the redlines of their performance (Xie and Salvendy, 2000[ 36 ]; Paxion et al, 2014[ 27 ]; Young et al, 2015[ 39 ]; Wascher et al, 2016[ 33 ]). On the other hand, the balance in the workload reduces the human error and increases the task performance of operators (Xie and Salvendy, 2000[ 36 ]; Yu et al, 2016[ 40 ]; Zhao et al, 2016[ 41 ]). Therefore, the concept of mental workload and mechanism of its effect on task performance in different human-machine systems is considered by practitioners and researchers in a variety of cognitive activities, such as conventional driving (Allahyari et al, 2014[ 1 ]; Hassanzadeh-Rangi et al, 2014[ 18 ]; Yan et al, 2019[ 37 ]), automated driving (Ko and Ji, 2018[ 22 ]), train driving (Balfe et al, 2017[ 6 ]), nuclear power plants (Choi et al, 2018[ 12 ]), advanced surgery programs (Cavuoto et al, 2017[ 9 ]), air traffic monitoring (Dasari et al, 2017[ 14 ]), control rooms (Melo et al, 2017[ 24 ]), workplace activities (Chen et al, 2017[ 11 ]), information technologies (Buettner, 2017[ 7 ]) and other complex human-machine systems (Xiao et al, 2015[ 35 ]).…”
Section: Introductionmentioning
confidence: 99%